Narrative temporal paradoxes in the "Shefrat Bilal" novel - an Applied study - Abu Ajami, Laila Ahmed; Al-Assad, Etimad Ibrahim Hassan (Journal of Arabic Language Sciences and Literature, 2024)
In this research entitled (Narrative Temporal Paradoxes in the "Shefrat Bilal" Novel – an Applied Study), we discussed temporal paradoxes (the techniques of retrieval and anticipation) in the "Shefrat Bilal" Novel - by the writer Ahmed Khairy Al-Omari, so we divided it into an introduction and three sections, then a conclusion with the most important results. In the introduction, we presented the topic, the reasons for choosing it, its goals, and the approach followed in it. After that, we looked at the concept of temporal paradoxes in the narrative with simple glimpses drawn from the novel. This was the first chapter, and the second chapter. We touched on the temporal intersection in the "Shefrat Bilal" Novel, comparing Bilal Al-Niwirki and Bilal Al-Habashi. So, we decided to rise to the threshold in the "Shefrat Bilal" Novel. It is a long-term internal anticipation. As for the third chapter, it is the essence of this applied study that extracts temporal paradoxes from the novel in their scope and breadth after discovering the indicator of the temporal paradox. One of the most important findings of this study is that the entire novel is based on temporal paradoxes. Dr. Ahmed Khairy Al-Omari used to base his novel on the paradox of preliminary preemptive time, when he began it with the message of the child Bilal to Amjad Al-Halwani. The message came with time paradoxes that paved the way for the course of events that fluctuate between these paradoxes. Paradoxes, which suggest that the technique of the retrieval paradox prevails over the "Shefrat Bilal" Novel. The temporal paradoxes (preemption and retrieval) would not have been in this clear and contributing form to building the events of the novel, had the author not adopted the temporal intersection between the time of the New York child Bilal (present time) and the time of Bilal bin Rabah Al-Habashi (the time of the distant past).